HUBUNGAN TINGKAT PENGETAHUAN IBU HAMIL TENTANG ANEMIA TERHADAP KEPATUHAN IBU HAMIL DALAM MENGKONSUMSI TABLET FE DI PUSKESMAS JAMBESARI KABUPATEN BONDOWOSO TAHUN 2023 - Husna, Rifqotul; Zakiyyah, Muthmainnah; Lestari, Dwi Anggun (NHM PRESS, 2024)
During pregnancy, anemia commonly occurs and is usually caused by iron deficiency, secondary to previous blood loss, or inadequate iron intake. Emergencies can occur during the childbirth process due to anemia. Anemia in pregnant women has adverse effects on both the mother and the fetus. The aim of this study was to determine the relationship between pregnant women's knowledge of anemia and their compliance in consuming Fe tablets at Jambesari Public Health Center, Bondowoso Regency in 2023. This research used a quantitative approach with a descriptive correlational design and a cross-sectional approach. The population consisted of 80 respondents, and random sampling technique was used. The majority of the respondent mothers at Jambesari Public Health Center, Bondowoso Regency, had good knowledge about anemia, with 69 respondents (86.2%), and they had compliant behavior, with 66 respondents (82.5%). The results of the Chi-Square Tests analysis showed a value of α<0.05, which was (0.000), indicating a significant relationship between pregnant women's knowledge of anemia and their compliance in consuming Fe tablets at Jambesari Public Health Center, Bondowoso Regency in 2023. Healthcare providers, especially midwives at Jambesari Public Health Center and other health centers, need to increase efforts in providing effective and comprehensive education to pregnant women about the importance of preventing and managing anemia during pregnancy. By providing accurate and supportive information, pregnant women's knowledge and awareness of anemia will improve.